983 LEARNING FROM THE EXPERIENCES OF NURSES IN CARE HOMES DURING COVID-19 (THRIVE STUDY): STEERING THE SHIP THROUGH THE STORM. (14th June 2022) - Birt, L; Lane, K; Corner, J; Sanderson, K; Deakins, A; Bunn, D
Abstract: Background: Nurses practising in older people's care homes are often the only trained nurse on shift, undertaking leadership roles while also supporting residents with complex clinical needs. The study aimed to explore Nursing and Midwifery Council (NMC)-registered nurses' experiences of working in older people's care homes during the COVID-19 pandemic. Method: Recruitment used direct contact with care homes, social media and links provided by national partners, then purposive sampling for age, gender, type of care home and location. Data collected through one-to-one on-line interviews using a topic guide developed collaboratively with care home nurses, focusing on how COVID-19 impacted on nurses' resilience and mental well-being. Data were analysed thematically. Results: 18 nurses interviewed between March–July 2021: female 16, majority aged between 46–55 years; mean time registered with NMC 19 years (range 18 months-45 years); one had not nursed residents with COVID-19. Preliminary findings indicate that nurses developed enhanced clinical skills, which increased their professional standing. Many nurses were in leadership roles responsible for processing and sharing rapidly-changing guidance, making judgements on how to manage infection risk within the home. Nurses reported balancing information-assimilation and reporting with providing direct care due to staff shortages. All nurses provided emotional support to other staff. They sought support from their peers, namely nurses inside and outside their workplace. As leaders, many of the nurses spoke about the emotional impact of having to manage relatives' expectations and make decisions on whether a relative could be with a dying resident. Conclusion: Understanding the types of support that might best increase resilience and well-being for nurses in care homes now and in the future is essential to maintain a healthy, stable workforce. Support for nurses will likely benefit other care workers either directly through wider roll-out, or indirectly through improved well-being of the nurse leaders.